Analysis Mandatory Policy of “Berkah Digital” Application in Murabâhah Financing at BMT Assafi'iyah Berkah Nasional Metro, Indonesia - Maulita, Ulan; Alawiyah, Ika Trisnawati (el-Jizya: Jurnal Ekonomi Islam, 2026)
This study aims to analyze the effectiveness of the mandatory policy requiring the use of the Berkah Digital application to optimize the distribution and supervision of murâbahah financing at BMT Assafiyah Berkah Nasional Metro. Digital transformation is seen as crucial to improving the operational efficiency of Islamic microfinance institutions. The research method used is a qualitative descriptive approach, with data collected through in-depth interviews, observations, and documentation. The results show that although these policies aim to speed up administration and increase transparency, on-the-ground practices are not yet fully optimal. The application's implementation has succeeded in facilitating systematic installment control. Still, its effectiveness is significantly hampered by the low digital literacy of senior members and by frequent network technical constraints. As a result, part of the supervision process is still carried out manually and has not been fully integrated according to the policy target. Overall, this policy provides a good foundation for digitalization, but requires an in-depth evaluation of the readiness of human resources and supporting infrastructure to ensure the optimization of murâbahah financing can be achieved in a truly accountable manner.